2013
DOI: 10.1093/jhered/est030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Differentiation of Bison (Bison bison) Subspecies and Cattle (Bos taurus) Breeds and Subspecies

Abstract: The genetic relationship of American plains bison (Bison bison bison) and wood bison (Bison bison athabascae) was quantified and compared with that among breeds and subspecies of cattle. Plains bison from 9 herds (N = 136), wood bison from 3 herds (N = 65), taurine cattle (Bos taurus taurus) from 14 breeds (N = 244), and indicine cattle (Bos taurus indicus) from 2 breeds (N = 53) were genotyped for 29 polymorphic microsatellite loci. Bayesian cluster analyses indicate 3 groups, 2 of which are plains bison and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Even though European bison are not domesticated, their genetic background [ 22 ] and morphology [ 23 ] is similar to domestic cattle Bos taurus , and the livestock sector has considerable experience with BCS schemes [ 24 , 25 ]. Today, the entire fertility and welfare management in professional dairy herds is based on such condition estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Even though European bison are not domesticated, their genetic background [ 22 ] and morphology [ 23 ] is similar to domestic cattle Bos taurus , and the livestock sector has considerable experience with BCS schemes [ 24 , 25 ]. Today, the entire fertility and welfare management in professional dairy herds is based on such condition estimates.…”
Section: Methodsmentioning
confidence: 99%
“…With a MaxEnt ecological niche modelling approach, we identified a large core area of highly suitable bison habitat from central Alberta, Canada, southward along the Rocky Mountains into the Great Plains, falling within the historic bison distribution mapped by Allen [3] and Roe [4] (Fig 1, 3). Of the two recognized ecotypes of North American bison [85,86], the MaxEnt model largely encompasses the range of the migratory "plains" variant that occurred in high numbers on the grasslands of the southern Great Plains. Traditional ecological knowledge and numerous accounts of early journalists provide evidence of plains bison herds numbering in the tens of thousands [30,87,88].…”
Section: Processes Limiting Historic Bison Distributionmentioning
confidence: 99%
“…BACKGROUND-Today, there are two, albeit disputed, subspecies of Bison (Cronin et al, 2013): 1) Bison bison bison are historically found in the Great Plains and elsewhere throughout much of North America, and 2) Bison bison athabascae are historically found north of 498N latitude in Canada and Alaska. This project does not address subspecies or species but focuses on the animal at the generic level.…”
Section: Resumen-los Fósiles Dementioning
confidence: 99%